Virtual reality in education breakthroughs in research and practice (IGI Global, 2019)
"This book is an essential reference source on the uses of virtual reality in classrooms with a focus on pedagogical and instructional outcomes and strategies. Highlighting a range of pertinent topics such as virtual 3-D learning, ethics in virtual reality, and educational technologies"--